2018
DOI: 10.1093/jpids/piy009
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and Pediatric Candidemia: Results From Population-Based Active Laboratory Surveillance in Four US Locations, 2009–2015

Abstract: The incidence of candidemia among neonates and infants declined after 2009 but remained stable from 2012 to 2015. Antifungal drug resistance is uncommon. Reasons for the lack of recent declines in neonatal and infant candidemia deserve further exploration. In this article, we describe the epidemiology of candidemia in children in the United States and on the basis of data collected as part of US Centers for Disease Control and Prevention active population-based surveillance. Trends in incidence, clinical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
6
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 46 publications
9
54
6
2
Order By: Relevance
“…In line with our findings, a recent US study also showed a decline in C. albicans with increasing age (11). The proportion of C. parapsilosis varies by setting and age, and was low in our setting Our finding that neonatal patients were acutely ill with a high proportion of ICU admission, mechanical ventilation, sepsis and TPN while older children most frequently had hematological diseases and solid cancers is in concordance with previous studies (4,11,19). The high burden of multi-morbidity have not previously been recognized and illustrates the heterogeneity of the pediatric candidemia population, and furthermore identify the underlying diseases for each age group.…”
Section: A C C E P T E Dsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with our findings, a recent US study also showed a decline in C. albicans with increasing age (11). The proportion of C. parapsilosis varies by setting and age, and was low in our setting Our finding that neonatal patients were acutely ill with a high proportion of ICU admission, mechanical ventilation, sepsis and TPN while older children most frequently had hematological diseases and solid cancers is in concordance with previous studies (4,11,19). The high burden of multi-morbidity have not previously been recognized and illustrates the heterogeneity of the pediatric candidemia population, and furthermore identify the underlying diseases for each age group.…”
Section: A C C E P T E Dsupporting
confidence: 93%
“…Conversely, the incidence of 10.2/100.000 population for infants <1 year was higher than reported in our neighboring countries Finland and Norway (6.9 and 7.5/100.000 population) (5,7), but markedly lower than in other population-based studies (15.7-96.4/100.000 population) (6,8,10,11,18). A considerable decline in incidence rates from 52.1/100,000 population in 2009 to 15.7/100.000 in 2015 was observed in a study from the US (11). An improvement in infection control precautions…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of neonatal and paediatric candidemia based on active laboratory surveillance in 4 US locations over the period 2009‐2015 showed that the overall incidence of candidemia in neonates decreased from 31.5 cases/100 000 births in 2009 to 10.7‐11.8 cases between 2012 and 2015. In infants, it decreased from 52.1 cases/100 000 in 2009 to 15.7‐17.5 cases between 2012 and 2015, while in older children it decreased steadily from 1.8 cases in 2009 to 0.8 in 2014 …”
Section: Epidemiology Of Paediatric Candidemiamentioning
confidence: 96%
“…In infants, it decreased from 52.1 cases/100 000 in 2009 to 15.7-17.5 cases between 2012 and 2015, while in older children it decreased steadily from 1.8 cases in 2009 to 0.8 in 2014. 21…”
mentioning
confidence: 99%